2020
DOI: 10.26508/lsa.202000662
|View full text |Cite
|
Sign up to set email alerts
|

Thymosin α1 protects from CTLA-4 intestinal immunopathology

Abstract: The advent of immune checkpoint inhibitors has represented a major boost in cancer therapy, but safety concerns are increasingly being recognized. Indeed, although beneficial at the tumor site, unlocking a safeguard mechanism of the immune response may trigger autoimmune-like effects at the periphery, thus making the safety of immune checkpoint inhibitors a research priority. Herein, we demonstrate that thymosin α1 (Tα1), an endogenous peptide with immunomodulatory activities, can protect mice from intestinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 49 publications
0
19
1
Order By: Relevance
“…In both DSS colitis and tumor models, 3-IAld was administered every other day at a dose of 18 mg/kg, starting 4 days before DSS treatment or in concomitance with tumor challenge, as already described. 28 Models of immune-mediated colitis NSG mice 8-10 weeks old were injected intraperitoneally with 10 7 human peripheral blood mononuclear cells (PBMCs). Human blood samples were obtained from healthy donors, and fresh PBMCs were isolated by density-gradient separation (Ficoll Paque Plus, GE Open access Healthcare).…”
Section: Methodsmentioning
confidence: 99%
“…In both DSS colitis and tumor models, 3-IAld was administered every other day at a dose of 18 mg/kg, starting 4 days before DSS treatment or in concomitance with tumor challenge, as already described. 28 Models of immune-mediated colitis NSG mice 8-10 weeks old were injected intraperitoneally with 10 7 human peripheral blood mononuclear cells (PBMCs). Human blood samples were obtained from healthy donors, and fresh PBMCs were isolated by density-gradient separation (Ficoll Paque Plus, GE Open access Healthcare).…”
Section: Methodsmentioning
confidence: 99%
“…The favorable combination of thymosin α1 with an anti-PD-1 antibody has been already postulated in an experimental setting in which low doses of thymosin α1, while being ineffective alone, increased the efficacy of an anti-PD-1 antibody in the lung metastasis melanoma model [ 19 ]. Moreover, several evidence converge in the suggestion that thymosin α1 represents a plausible candidate to improve the safety and the efficacy profile of ICI [ 20 ], and, in particular, a preclinical study has shown the protective role of thymosin α1 from intestinal toxicity in a murine model of ICI-induced colitis [ 21 ].…”
Section: Thymosin α1mentioning
confidence: 99%
“…Another example is represented by thymosin α1, an endogenous thymic peptide with a wide range of immunomodulatory activities [ 66 ] and the capacity to balance a dysregulated immune response in a context-dependent manner. Indeed, thymosin α1 could either be immunostimulatory, such as in cancer and immune deficiency, or promote tolerance in inflammatory conditions, for instance by inducing the indoleamine 2,3-dioxygenase 1 pathway [ 67 , 68 , 69 ] or promoting autophagy [ 68 ]. The latter process is increasingly being recognized as a regulator of lung health and protection against microbial infection, with potential relevance for a variety of lung diseases, including COVID-19 [ 70 ].…”
Section: Restoring Immune Homeostasis In Covid-19 To Prevent Capamentioning
confidence: 99%